A techno-economic and environmental analysis of co-firing implementation using coal and wood bark blend at circulating fluidized bed boiler - Cahyo, Nur; Sulistyowati, Desy; Rahmanta, Mujammil Asdhiyoga; Felani, Muhamad Iqbal; Soleh, Mochamad; Paryanto, Paryanto; Prismantoko, Adi; Hariana, Hariana (Center of Biomass & Renewable Energy (CBIORE), 2024)
The study aimed to explore the effects of biomass co-firing of coal using acacia wood bark at circulating fluidized bed (CFB) boiler coal-fired power plant with 110 MWe capacity. The analysis focused on main equipment parameters, including the potential for slagging, fouling, corrosion, agglomeration, fuel cost, and specific environmental factors. Initially, coal and acacia wood bark fuel were blended at a 3% mass ratio, with calorific values of 8.59 MJ/kg and 16.59 MJ/kg, respectively. The corrosion due to chlorine and slagging potential when using wood bark was grouped into the minor and medium categories. The results showed that co-firing at approximately 3% mass ratio contributed to changes in the upper furnace temperature due to the variation in heating value, high total humidity, and a less homogeneous particle size distribution. Significant differences were also observed in the temperature of the lower furnace area, showing the presence of a foreign object covering the nozzle, which disturbed the ignition process. A comparison of the seal pot temperature showed imbalances as observed from the temperature indicators installed on both sides of boiler, with specific fuel consumption (SFC) increasing by approximately 0.17%. During the performance test, the price of acacia wood bark was 0.034 USD/kg, resulting in fuel cost of 0.023355 USD/kWh, adding 0.061 cent/kWh to coal firing cost. Despite co-firing, the byproducts of the combustion process, such as SO2 and NOx, still met environmental quality standards in accordance with government regulations. However, a comprehensive medium- and long-term impact evaluation study should be carried out to implement co-firing operations using acacia wood bark at coal-fired power plant. Based on the characteristics, such as low calorific value, with high ash, total moisture, and alkali, acacia wood bark showed an increased potential to cause slagging and fouling.